Spatial molecular interferometry via multidimensional high-harmonic spectroscopy - Uzan, Ayelet J.; Soifer, Hadas; Pedatzur, Oren; Clergerie, Alex; Larroque, Sylvain; Bruner, Barry D.; Pons, Bernard; Ivanov, Misha; Smirnova, Olga; Dudovich, Nirit (Nature Photonics, 2020)
Interferometry is a basic tool to resolve coherent properties in a wide range of light or matter wave phenomena. In the strong-field regime, interferometry serves as a fundamental building block in revealing ultrafast electron dynamics. In this work we manipulate strong-field-driven electron trajectories and probe the coherence of a molecular wavefunction by inducing an interferometer on a microscopic level. The two arms of the interferometer are controlled by a two-colour field, while the interference pattern is read via advanced, three-dimensional high-harmonic spectroscopy. This scheme recovers the spectral phase information associated with the structure of molecular orbitals, as well as the spatial properties of the interaction itself. Zooming into one of the most fundamental strong-field phenomena—field-induced tunnel ionization—we reconstruct the angle at which the electronic wavefunction tunnels through the barrier and follow its evolution with attosecond precision.
CRIS-Team Scopus Importer:2023-04-20